The role of stem cells and WNT signalling pathway in renal cell carcinoma - Madlala, Siphelele Clifford (Division of Anatomical Pathology, 2020)
Introduction: Renal cell carcinoma (RCC) accounts for 87% of all kidney cancers. Despite advances in diagnostic techniques and management, renal cell carcinoma remains a lethal tumour accounting for substantial mortality and morbidity. The poor prognosis arises from metastasis, chemoradiation resistance and disease relapse. Cancer stem cells, a subpopulation of tumour cells with capacity to self-renew and reconstitute tumour heterogeneity have been implicated as the root cause of poor prognosis. Therefore, a better understanding of biomarkers of cancer stem cells will be useful for risk stratification, prognostication and may lead to novel targeted therapies that will ultimately alter the management of many patients. Aims and objectives: To review the morphological subtypes of renal cell carcinomas diagnosed in the Division of Anatomical Pathology, National Health Laboratory Service, Groote Schuur Hospital over a 10-year period. To identify cancer stem cells in various histopathological subtypes of renal cell carcinoma using immunohistochemical markers (CD133 and CD105). To review the WNT signalling pathway in renal cell carcinomas using selected protein expression by immunohistochemistry (β-Catenin).Materials and methods: Ten-year retrospective study in which sixty-four cases of renal cell carcinoma were retrieved and reviewed. Four immunohistochemical stains (β-catenin, HIF-1α, CD133 and CD105) were performed and scored in tumour tissue. Data were analysed to determine if there was any correlation between expression of the biomarkers and the histopathological subtypes of renal cell carcinoma. Results: The mean age of the patients was 56-years (range, 35 to 81 years). Females constituted just over half (52%, n = 33) of the study patients. All 64 cases were confirmed as renal cell carcinomas, with 29 (45%) clear cell renal cell carcinomas, 14 (22%) papillary renal cell carcinomas, 9(14%) chromophobe renal cell carcinomas, 9 (14%) multicystic renal cell carcinomas and 3 (5%) sarcomatoid renal cell carcinomas. Ten (16%) cases showed abnormal β-Catenin cytoplasmic localisation. The majority of cases (n=6, 60%) showing abnormal β-Catenin localisation were clear cell renal cell carcinomas. However, there was no significant correlation between abnormal and normal β-Catenin localisation and RCC histopathological subtype (p = 0.766). CD133 immunohistochemical studies showed low expression in 52 (81 %) cases and high expression in 12 (19 %) cases. There was no correlation between low and high CD133 expression and histopathological RCC subtype (P = 0.800). CD105 immunostaining showed tumour cell immunopositivity in one case of clear cell renal cell carcinoma whilst the rest of the cases were negative. The low, moderate and high microvascular density categories had 24, 10 and 32 cases respectively. There was no significant correlation between low, moderate, and high microvascular densities and the histopathological RCC subtype (P = 0.320). HIF-1α immunohistochemical studies showed low expression in 39 (61 %) cases and high expression in 25 (39 %) cases. There was no significant correlation between levels of HIF-1α expression and the histopathological RCC subtype (P =0.972).Conclusion: Within the power limitations of this small study,β-catenin abnormal expression, microvascular densities and levels cytoplasmic CD133 and HIF-1α were not associated with any histopathological subtype of renal cell carcinoma.